PEMBELAJARAN PAI DI SEKOLAH DAN MADRASAH: ANTARA CITA DAN REALITA - Nasution, Sri Mulyani; Rosyada, Dede (Pascasarjana Universitas Islam Jakarta, 2022)
Islamic religious education is basically education that aims to form a complete Muslim person, develop all human potential both physically and spiritually, and foster a harmonious relationship between each person and Allah SWT. The implementation of religious education that takes place in schools today can be said to still experience many weaknesses. The reality that occurs in the field is still not able to meet the ideal conditions aspired to. Innovations that are able to bridge the barriers that block reality towards ideal conditions certainly need to be created, especially in the face of today's rapid changes. This type of research is library research, library research is research carried out using literature (library), either in the form of books, notes, or reports on research results from previous studies. Flexibility, adaptability, optimism, and teamwork determine the teacher's approach to change. Efforts to improve the quality of teachers can be done by increasing discipline, and knowledge and providing training. In addition, education leaders must support and encourage teachers to implement appropriate changes; 2) Ensure that changes made by teachers are sustainable over time; 3) Ensure that changes can be transmitted to other teachers.